Bilateral Acute Macular Neuroretinopathy (AMN) after COVID-19 and its Clinical Course - Bartsch, Alexander; Skornia, Adam; Mardin, Christian; Hohberger, Bettina (Klinische Monatsblätter für Augenheilkunde, 2023)
Acute macular neuroretinopathy (AMN) is a rare disease entity. It is mainly observed in young women with a history of influenza-like infection or who have been taking oral contraceptives for several years. Patients typically describe subjective visual deterioration and mono- or bilateral paracentral relative scotomas. In some cases, funduscopic ophthalmic examination may reveal subtle sharply demarcated flat lesions of reddish-brown or orange colour in the macular region. Diagnosis is usually made by near-infrared fundus imaging which shows hyporeflective areas, and SD-OCT imaging which manifests changes in the outer retinal layers. In the following, three patient cases with bilateral AMN are described which occurred in direct temporal relationship to a recent SARS-CoV-2 infection.
CRIS-Team WoS Importer:2023-06-02
Keywords: akute makuläre; Neuroretinopathie; SD-OCT; Retina; COVID-19; SARS-CoV-2